The Portrayal of an Iranian Queer Muslim Teenager in Arvin Ahmadi’s How It All Blew Up - Abimayu, Muhamad Tri Satria (UIN Syarif Hidayatullah Jakarta, 2022)
This research examines the representation of an Iranian queer Muslim teenager in Arvin Ahmadi's How It All Blew Up. It also evaluates how the novel describes the sufferings of an Iranian queer Muslim teenager through symbolism, which Ahmadi uses as his aesthetic strategies. This research is descriptive qualitative, which examines the primary text by using close textual analysis. This research engages with Stuart Hall's theory of representation and Chris Barker's queer theory. The research investigates the symbolism representing the sufferings of an Iranian queer Muslim teenager and what aesthetic strategies the author uses to question mainstream society, which tends to exclude a queer teenager from “normal” belonging. Indeed, the analysis is engaged with Stuart Hall's theory of representation and Chris Barker's queer theory. This research discovered five representations of the protagonist character in the novel, namely Amir is represented as an Iranian queer Muslim that was born to an Iranian Muslim immigrant family, an Iranian queer Muslim that grew up in a Muslim family that did not strictly implement Islamic teachings, an irreligious Iranian queer Muslim, an Iranian queer Muslim that was attracted to people of the same sex, and an Iranian queer Muslim that struggled with his family's acceptance of his queerness. Indeed, this research discovers four symbols that are used to represent the suffering of an Iranian queer Muslim teenager, including the symbol of fortress, tunnel, tattoo, and wall. Thus, Ahmadi’s novel reveals how a queer Muslim teenager struggles to fight for his rights to be acknowledged and appreciated in the ideas of “normality” and social belonging.